An Integrated Approach to Value Added Tax in the Emerging Economic Scenario - Chandel, Kulbhushan; Narta, S. S.; Sood, Sudhanshu (Indian Journal of Marketing, 2006)
The Value-Added Tax (VAT) is a tax imposed on business at all levels of production and based on the increase in value provided at each level. It is a general consumption tax assessed on the value, added to goods and services. It is a general tax that applies in principle to all commercial activities involving the production and distribution of goods and the provisions of services. It is a consumption tax because it is born ultimately by the final consumer. It is not a charge on companies. It is charged as a percentage of price, which means that the actual tax burden is visible at each stage in the production and distribution chain. It is collected fractionally via a system of deductions whereby taxable persons can deduct VAT liability from the amount of tax, they have paid to other taxable persons on purchases for their business activities. This mechanism ensures that the tax is neutral regardless of how many transactions are involved.